Atrazine derangement of GLUT-4 and Insulin metabolism and the ameliorative effect of Virgin coconut oil in male wistar rats (International Journal of Current Research in Physiology and Pharmacology, 2021)
We assessed the ameliorative effect of Virgin Coconut Oil following atrazine-induced metabolic derangement in rats. Adult male wistar rats weighing 180-200g were used; randomly separated into two major groups. Thirty-five rats in the test group were randomly divided into five sub-groups of 7 rats per sub-group and treated thus: Sub-group (SG) 1, 2 and 3 received 10ml/kg of distilled water, 10ml/kg VCO, 123mg/kg of Atrazine respectively, SG4 was diabetic control; SG 5 was the diabetic group treated with 10ml/kg of VCO for 2 weeks, after which the animals were sacrificed and blood collected for analysis. 35 rats for the recovery group were also divided into 5 sub-groups of 7 rats per sub-group and were treated; SG 1, 2, 3, 4 and 5 received 10ml/kg distilled water, 10ml/kg VCO, 123mg/kg of ATZ respectively. After 2 weeks, the animals were re-treated thus: SG 1,2,3,4 and 5 received 10ml/kg of distilled water, 10ml/kg of VCO, 123mg/kg of ATZ, 10ml/kg VCO and 10ml/kg distilled water respectively. After 2 weeks, the animals were also sacrificed and blood collected for analysis. ATZ reduced serum insulin and a reduced expression of GLUT4. VCO restored GLUT4 levels but did not significantly restore the insulin to the normal levels
Keywords: GLUT-4; Insulin; Atrazine; Virgin Coconut Oil; Diabetes; Glucose